DEVELOPMENT OF THE COMBINED SILAGE FOR IMPROVING THE EJACULATES QUALITY IN BREEDING BOARS - Ibraimova, Zh.K.; Rustenov, A.R.; Eleugaliyeva, N.Zh.; Oleksievich, E.A. (Eurasian Journal of Applied Biotechnology, 2013)
A breeding boar is required to be healthy, strong, active, of breeding conditions. When mating a boar allocates up to 500 cm3 of sperm. Sperm is of good quality only in the case if the boar is properly cared and fed. In the case of poor feeding of boars there is observed eildness of dams and a large percentage of overlaps. The boars diet must be valuable regarding content of protein, minerals and vitamins. The combined silage is an important component for improving biological value of diets in winter conditions. While their preparation there are used cobs of maize, wet corn, melons, good - quality wastes, green mass, alfalfa meal and etc. Feed ingredients ratio is determined by availability of raw materials. However, there should be obeyed the following general requirements: moisture of the ensilaging forage mixture - 70-80%; a good mixing of the components during loading in silo constructions; careful sealing; nutrient value of 1 kg of the combined silage should be at least 0.25 fodder units. The content of digestible protein - 20 gr, carotene -20 mg, fiber - not more than 60 gr. To improve the quality parameters of the boars’ sperm, there have been developed and studied different variants of the combined silage with with Lactobacillus plantarum-52 biopreservant. In the composition of combined silage were included - maize, pumpkin, and alfalfa and grape pomace in various combinations. It is found that the most positive qualitative changes in the boars’ sperm have occurred in cases, where, together with the basic diet, a combined silage, made of corn, alfalfa, grape pomace and treated with Lactobacillus plantarum-52 biopreservant, had been included. At this point, volume of ejaculate has increased (%) - 13.4, the concentration of spermatozoa - 3.6, an absolute indicator of sperm viability - of 37.7, preservation of intracellular sulfhydryl groups - 6.9, sow fertility - by 14.2% and, conversely, decreased the number of gametes with damaged acrosome - by 4.4%.